Control of a water delivery canal with cooperative distributed MPC - Igreja, J.M. (2013)
This article addresses the problem of controlling pool levels in a water delivery canal using a novel cooperative distributed MPC control algorithm that incorporates stability constraints. According to a distributed control strategy, a local control agent is associated to all canal gates (actuators). In order to achieve cooperative action, each control agent computes the corresponding gate position (manipulated variable) by performing the minimization of a cost function that considers not only its local control objectives, but also the ones of their immediate neighbors. For this purpose, a MPC algorithm with stability constraints is used (SIORHC). At the beginning of each sampling interval, local control agents exchange information with their neighbors and adjust their decision in an iterative way. The resulting distributed MPC is denoted D-SIORHC and yields a stable closed-loop. Experimental results are provided to show the influence of the controller configuration parameters on the resulting performance.